Cardioneuroablation for Treatment of Atrioventricular Block. (1st September 2021) - Aksu, Tolga; Gopinathannair, Rakesh; Bozyel, Serdar; Yalin, Kivanc; Gupta, Dhiraj
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The contribution of autonomic influences to atrioventricular block (AVB) is unclear. Although cardioneuroablation has been used to treat cardioinhibitory vasovagal syncope, its role in treating functional paroxysmal and persistent AVB has not been formally evaluated. Methods: We used a stepwise protocol in 241 consecutive patients presenting with symptomatic AVB to identify 31 (12.9%) patients with functional or vagally mediated AVB. All patients had episode(s) of syncope in previous 12 months, and AVB was persistent in 17 (54.8%) patients. All 31 patients received targeted catheter-based cardioneuroablation, and their follow-up outcomes were evaluated with serial Holter monitoring. Results: Twenty-eight patients received biatrial or left-sided cardioneuroablation while 3 received only right-sided cardioneuroablation because of structural factors that precluded safe attempts at transseptal puncture. Procedural success, as defined as acute reversal of AVB and complete abolition of atropine response, was achieved in 30 (96.7%) cases, while the remaining patient received a pacemaker. Over a mean follow-up of 19.3±15 months, AVB episodes were observed in 2 (6.7%) of 30 cases, and 3 (9.6%) patients required pacemaker implantation during follow-up. Conclusions: Functional AVB can be identified in a minority of patients presenting with high-grade AVB. Cardioneuroablation for these patients results in encouraging medium-term outcomes.